Fungible Life : Experiment in the Asian City of Life - Ong, Aihwa (Book collections on Project MUSE., 2016)
In Fungible Life Aihwa Ong traces the revolutionary scientific developments in Asia by investigating how biomedical centers in Biopolis, Singapore and China mobilize ethnicized ""Asian"" bodies and health data for genomic research.